Multiple Episodes of Fluid Infiltration Along a Single Metasomatic Channel in Metacarbonates (Mogok Metamorphic Belt, Myanmar) and Implications for CO2 Release in Orogenic Belts. Issue 1 (29th December 2020) - Guo, Shun; Chu, Xu; Hermann, Joerg; Chen, Yi; Li, Qiuli; Wu, Fuyuan; Liu, Chuanzhou; Sein, Kyaing
Abstract: Fluid infiltration into metacarbonates is a key mechanism to induce orogenic decarbonation, which influences the global carbon cycle and long‐term climate evolution. Little is known regarding the fluid pathways during episodic infiltration events and how flow patterns control time‐integrated CO2 outflux. We investigate the "vein‐like" polycrystalline mineral reaction zones (PMRZs) in dolomite marbles (Mogok metamorphic belt, Myanmar), which are formed by metasomatism via the infiltration of Si–Al–K–Ti–Zr‐bearing fluids. The petrographic textures and mineral U–Pb chronology reveal three episodes of fluid influx in a single PMRZ: (1) the initial episode (Stage‐I) transformed most dolomite into Mg‐rich silicates/oxides and calcite at ∼35–36 Ma indicated by baddeleyite cores; (2) baddeleyite rims gave ages of ∼23–24 Ma, representing a subsequent infiltration episode (Stage‐II) that modified Stage‐I minerals via a dissolution–precipitation mechanism; (3) the final episode (Stage‐III) is recorded by zircon replacing baddeleyite, which yielded ages of ∼17 Ma. Stage‐III fluid has a higher SiO2 activity and X CO 2 [CO2 /(CO2  + H2 O)] than Stage‐I/Stage‐II fluids. Thermodynamic and mass‐balance analyses indicate that Stage‐I infiltration causes >62–67% loss of CO2 by both dolomite‐consuming reactions and calcite dissolution, whereas the latter two infiltration episodes induce <12–18% loss of CO2 via calcite dissolution. Our results provide compelling evidence that repeated episodes of infiltration (each separated in time by 7–13 Ma) occurred along a single channel in marbles. The initial infiltration episode may create high‐permeability regions, offering favorable channels for later‐stage fluids that transfer obviously less CO2 than the initial metasomatism. This considerably complicates a quantitative assessment of CO2 liberation from metacarbonates during orogenesis. Key Points: Gem‐bearing reaction zones in Mogok marbles record three episodes of fluid infiltration each separated in time by 7–13 Ma Initial fluid infiltration drives dolomite‐consuming reactions and produces high‐permeability zones that channelize later fluid transport Effect of multiple fluid infiltration episodes on metamorphic CO2 release from marbles in orogenic belts is assessed